2017
DOI: 10.3389/fmicb.2017.01086
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Live-Attenuated H9N2 Influenza Vaccine Candidates Containing NS1 Truncations against H9N2 Avian Influenza Viruses

Abstract: H9N2 avian influenza virus is a zoonotic agent with a broad host range that can contribute genetic information to H5 or H7N9 subtype viruses, which are significant threats to both humans and birds. Thus, there is a great need for a vaccine to control H9N2 avian influenza. Three mutant viruses of an H9N2 virus A/chicken/Taixing/10/2010 (rTX-NS1-73, rTX-NS1-100, and rTX-NS1-128) were constructed with different NS1 gene truncations and confirmed by western blot analysis. The genetic stability, pathogenicity, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…H9N2 AIVs A/chicken/Shanghai/F/98 (H9N2), A/chicken/Taixing/10/2010 (H9N2, rTX), and the NS1 truncated virus (rTX-NS1-128) ( Chen et al, 2017 ) were identified and stored by our laboratory and were cultured in the 9- to 11-day-old embryonated SPF chicken eggs at 37°C. Allantoic fluids were harvested 72 h post-inoculation and stored at −70°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…H9N2 AIVs A/chicken/Shanghai/F/98 (H9N2), A/chicken/Taixing/10/2010 (H9N2, rTX), and the NS1 truncated virus (rTX-NS1-128) ( Chen et al, 2017 ) were identified and stored by our laboratory and were cultured in the 9- to 11-day-old embryonated SPF chicken eggs at 37°C. Allantoic fluids were harvested 72 h post-inoculation and stored at −70°C.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, H9N2 live attenuated vaccine candidate strain with a truncated NS1 gene was constructed, verified by animal experiments that provide good protection for both specific pathogen-free (SPF) chickens ( Chen et al, 2017 ). On the basis of this vaccine virus (rTX-NS1-128 strain), the HA packaging signal, including NCR, the 80 nucleotides (nt) of 5′ORF, and the 9 nt of 3′ORF ( Watanabe et al, 2003 ), and the NS packaging signal, including NCR, 150 nt of 5′ORF, and 150 nt of 3′ORF ( Fujii et al, 2005 ), were exchanged to avoid viral recombination and to construct safe and high-efficiency live attenuated vaccines.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mutant virus of H9N2 subtype with NS1-128 truncation was more immunogenic than the corresponding inactivated vaccine and protected chickens from challenge by homologous and heterologous H9N2 avian influenza viruses [38].…”
Section: Vaccines With Truncated Ns1 Genementioning
confidence: 97%
“…The current MLIVs are based on apathogenic influenza viruses, and attenuation is, e.g. achieved by using truncated NS1 proteins 21 or restricted replication capacities due to cold-adaptation 22 or the introduction of elastasespecific cleavage sites into the HA precursor protein 23 . Although cold-adapted MLIVs have been licensed for several years for use in humans, there are no MLIVs licensed for poultry yet, and only two types of vector-based live vaccines are on the market 18 .…”
Section: Introductionmentioning
confidence: 99%